Road Congestion and Incident Duration - Martin W. Adler; Jos van Ommeren; Piet Rietveld (Tinbergen Institute, 2013)
Non-recurrent congestion is frequently caused by accidents and other incidents. We estimate the causal effect of incident duration on drivers' time losses through changes in non-recurrent road congestion on Dutch highways. We demonstrate that incident duration has a strong positive, but concave, effect on non-recurrent congestion. The duration elasticity of non-recurrent congestion is about 0.40 implying that a one minute duration reduction generates a exteuro60 gain per incident. We also show that at locations with high levels of recurrent congestion, non-recurrent congestion levels are considerably higher. At very congested locations, the benefit of reducing the incident duration by one minute is about exteuro500 per incident. Public policies that prioritize duration reductions at congested locations are therefore more beneficial.
Keywords: R4; 330; congestion; vehicle-loss-hours; incident duration; accidents